OFFSHORISATION OF THE ECONOMIES OF THE BRICS COUNTRIES: COMPARATIVE ANALYSIS - B. Loguinov (Publishing House of the State University of Management, 2016)
In the article the comparative analysis of the offshoring level of the BRICS economies is made. The author also enumerated and revealed the content of the main imbalances of the international cooperation in credit and finance spheres between these countries and the West. As pointed out in the article, each BRICS country has “its own” offshores which are chosen by the subjects of national economies.